2022
DOI: 10.1177/23969873221138197
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of the combined brain-cardiac CT protocol on prediction of atrial fibrillation after stroke

Abstract: Introduction: Atrial fibrillation (AF) is one of the most common causes of ischemic stroke. It is essential to target patients at highest risk of AF detected after stroke (AFDAS), who should benefit from a prolonged rhythm screening strategy. Cardiac-CT angiography (CCTA) was added to the stroke protocol used in our institution in 2018. We sought to assess, for AFDAS, the predictive value of atrial cardiopathy markers by a CCTA performed on admission for acute ischemic stroke. Patients and Methods: From Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Tachycardia-associated arrhythmias, especially AF, are more frequent than bradycardias [15,26]. The incidence of AF following AIS is approximately 5-24% [21][22][23][24]. Consistent with the above-mentioned results, the incidence of AF detected after stroke (AFDAS) was higher in strokes involving the right insula (39%) than in strokes involving the left insula (4%) [61].…”
Section: Electrocardiographic Changes and Cardiac Arrhythmiasmentioning
confidence: 59%
“…Tachycardia-associated arrhythmias, especially AF, are more frequent than bradycardias [15,26]. The incidence of AF following AIS is approximately 5-24% [21][22][23][24]. Consistent with the above-mentioned results, the incidence of AF detected after stroke (AFDAS) was higher in strokes involving the right insula (39%) than in strokes involving the left insula (4%) [61].…”
Section: Electrocardiographic Changes and Cardiac Arrhythmiasmentioning
confidence: 59%
“…The predictive value of left atrial dilatation has already been demonstrated in our previous work on the role of cardiac CT angiography in the acute stroke imaging protocol. 34 These results taken together suggest that AC as defined in ARCADIA trial may lack sensitivity and specificity to target the patients who will benefit from an anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 97%
“… 1 , 5 , 7 , 21 Information on acute cardiac CT may also be used to predict occurrence of atrial fibrillation in patients with stroke. 22 …”
Section: Discussionmentioning
confidence: 99%